Consumer protection for sale of goods: A Malaysian perspective - Masum, Ahmad; Md Dahlan, Nuarrual Hilal; Nafees, Seeni Mohamed; Kyaw, Hla Win (2015)
Consumer protection is designed to promote and protect interests of consumers.As consumers always have a weak bargaining power, there is every need to protect them through adequate and effective laws (Yusoff, Ismail, Markom, & Zakuan, 2015). In today's challenging environment, consumers have to deal with current technology, mass-marketing tactics, high-pressure salesmanship and sharp advertising (Sabri, 2014).Malaysian market is not free from these challenges.Consumer protection is aimed at upholding justice and fairness in all commercial transactions between purchaser consumers and sellers or manufacturers.Consumer protection seems to alleviate the sufferings of consumers who are at a disadvantage in the market place.In view of the importance of protecting the basic rights of a consumer, the United Nations Assembly adopted the United Nations Guidelines for Consumer Protection on 9 April 1985 (Wan Jusoh, Othman, Nuruddin, & Ahmad, 2001).Since then, United Nations member countries have used these guidelines as their reference and have passed consumer protection or related legislations.In Malaysia, the main legislations governing the supply of goods are the Sale of Goods Act 1957 (SOGA) and the Consumer Protection Act 1999 (CPA). Despite the availability of such protection, nevertheless in the area of supply of goods, freedom of contract and caveat emptor still remain predominantly the underlying concepts in consumer contracts in Malaysia.The objective of this paper is to examine the existing Malaysian laws dealing with the sale of goods mainly SOGA and CPA, especially in terms of their adequacy in protecting consumers.The paper argues that the existing Malaysian laws, especially SOGA is not a consumer protection oriented piece of legislation. Many of its principles are based on the common law principles during the 1 8th and 19th centuries during which freedom of contract and laissez faire were widely practiced (Yusoff et al., 2015).Hence, this Act contains provisions which defeat consumer protection expectations and interests.On the other hand, the CPA being supplemental and without prejudice to any other law regulating contractual relations has indeed reduced the effectiveness of this long awaited legislation (Yusoff, Ismail, Aziz, Isa & Talib, 201 3).